2006
DOI: 10.2165/00007256-200636080-00001
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Tibial Torque and Knee Flexion Angle

Abstract: Knee injuries are common in sports activities. Understanding the mechanisms of injury allows for better treatment of these injuries and for the development of effective prevention programmes. Tibial torque and knee flexion angle have been associated with several mechanisms of injury in the knee. This article focuses on the injury to the anterior cruciate ligament (ACL), the posterior cruciate ligament (PCL) and the meniscus of the knee as they relate to knee flexion angle and tibial torque. Hyperflexion and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 36 publications
1
49
0
2
Order By: Relevance
“…Earlier studies have also reported reduced agonist activation during voluntary contractions at more extended knee angles [4,20,30,31], and this effect is thought to be a neural mechanism that protects the knee joint near full extension, where loading of the anterior cruciate ligament is greatest [32].…”
Section: Discussionmentioning
confidence: 90%
“…Earlier studies have also reported reduced agonist activation during voluntary contractions at more extended knee angles [4,20,30,31], and this effect is thought to be a neural mechanism that protects the knee joint near full extension, where loading of the anterior cruciate ligament is greatest [32].…”
Section: Discussionmentioning
confidence: 90%
“…38,46 Our systematic review is limited by the fact that most of the findings were derived from a very small number of studies. This was, in part, the result of excluding articles based on study design 3,9,10,12,38,47,49,[51][52][53]63,64,66 and the age of participants. 13,30,31,36,37,40,44,54,57,60 For a factor to be considered as a "risk" for meniscal tears, the prospective and retrospective period of exposure to the risk had to be sufficiently long.…”
Section: Discussionmentioning
confidence: 99%
“…When assessed on a lateral radiograph, a high-degree measurement error can exacerbate the variability [16,26]. It remains unclear whether noncontact ACL injury is a result of a greater medial PTS, lateral PTS, or both [6,39,43]. Regardless of which plateau is associated with an injury risk, the menisci play a role in AP knee stability and may modify this stability when injured or resected [25,36].…”
Section: Introductionmentioning
confidence: 99%